2016
DOI: 10.21273/horttech03443-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cool-season Vegetable Rotations in Organic Production

Abstract: Certified organic production is challenging in the southeastern United States due to high weed, insect, and disease pressure. Maintaining and building soil organic carbon in midscale organic production systems can also be difficult due to the warm, moist conditions that promote decomposition. Focusing on cool-season cash crops paired with warm-season cover crops may help alleviate these production problems. This 3-year study (2011–13) evaluated two vegetable rotations of cool-season crops with cover cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Differences among planting dates and cultivar type did not appear to have a major or consistent influence on the average marketable yield of fall/winter broccoli grown under our high tunnel system, although the cultivar 'Imperial' was slightly quicker to mature (1 week) compared with 'Belstar' and 'Fiesta'. In addition, all planting dates and cultivars demonstrated a high percentage of marketability, and our yields were equal or greater than another organic open field broccoli study conducted at the same location in Georgia (Boyhan et al, 2016). There were no indications of damage to the either broccoli or cauliflower heads grown under the high tunnels because of cold temperatures during the experimental timeframe, although some leaf tissue showed signs of frost damage later in the season.…”
Section: Discussionmentioning
confidence: 44%
“…Differences among planting dates and cultivar type did not appear to have a major or consistent influence on the average marketable yield of fall/winter broccoli grown under our high tunnel system, although the cultivar 'Imperial' was slightly quicker to mature (1 week) compared with 'Belstar' and 'Fiesta'. In addition, all planting dates and cultivars demonstrated a high percentage of marketability, and our yields were equal or greater than another organic open field broccoli study conducted at the same location in Georgia (Boyhan et al, 2016). There were no indications of damage to the either broccoli or cauliflower heads grown under the high tunnels because of cold temperatures during the experimental timeframe, although some leaf tissue showed signs of frost damage later in the season.…”
Section: Discussionmentioning
confidence: 44%
“…Here, we examine one field study of a simplified crop rotation (reported in full in Boyhan et al. ) to suggest that this shift may also allow small‐acreage producers to maintain their commitment to “sustainable” agriculture by identifying crop rotations that maintain or build soil health while resulting in harvests that are potentially profitable. However, crop rotations that can serve wholesale markets while maintaining production values (organic, building soil health) are not a one‐size‐fits‐all prospect.…”
Section: Resultsmentioning
confidence: 99%
“…Each rotation included three blocks (e.g., ABC , BCA , and CAB) of four replicates, grown in a continuous three‐year cycle, with 12 plots per rotation and 24 plots total (Boyhan et al. ).…”
Section: Case Study: Field‐testing a Mid‐scale Regionally Adapted Smentioning
confidence: 99%
See 2 more Smart Citations